Teaching and learning English in the Arabic-speaking world - Bailey, Kathleen M.; Damerow, Ryan M. (New York : Routledge, 2014)
'Co-published with The International Research Foundation for English Language Education (TIRF)An important contribution to the emerging body of research-based knowledge about teaching English to native speakers of Arabic, this volume presents empirical studies carried out in Egypt, Lebanon, Oman, Palestine, Saudi Arabia, and the United Arab Emirates (UAE ) region which has gained notable attention in the past few decades. Each chapter addresses an issue of current concern, and each includes implications for policy, practice, and future research. Nine chapter authors are Sheikh Nahayan Fellows ecipients of doctoral fellowships from The International Research Foundation for English Language Education (TIRF). This volume is the first in the Global Research on Teaching and Learning English Series, co-published by Routledge and TIRF'--
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Arabic speakers; English language -- Study and teaching -- Arab countries; English language -- Study and teaching -- Middle East